Most used nursing diagnoses in confirmed cases of covid-19 in Brazil (Research, Society and Development, 2021)
When the patient progresses to the severe condition of covid-19, the nurse must systematize, plan and direct nursing care so that the patient's recovery occurs. Thus, this study has the central objective of identifying the most frequent nursing diagnoses in patients contaminated by covid-19. The study was carried out through a literature review with a descriptive and qualitative approach, in digital libraries, which allow a search in their own databases using standardized descriptors. It was possible to identify 12 frequent diagnoses in patients with covid-19, which are: health promotion: ineffective protection, risk of electrolyte imbalance, diarrhea, decreased cardiac output, spiritual distress, related hyperthermia, related acute pain. Finally, there was a shortage of national publications on the topic addressed in this research, so authors expect this study to contribute to the development of new research related to nursing diagnoses in patients affected by covid-19. When properly applied, the ND has a positive impact on nursing care and contributes to a better patient's recovery, in addition to avoiding unnecessary interventions.